The impact of perceived safety, weather condition and convenience on motorcycle helmet use: The mediating role of traffic law enforcement and road safety education - Raymond Akuh; Martin Donani; Stephen Okyere; Emmanuel Kojo Gyamfi (IATSS Research, 2023)
Despite numerous studies on motorcycle safety, especially the compliance of helmet use laws in both developed and developing countries across the globe, little is known about the mediating role of traffic law enforcement and road safety education specifically on the relationship between helmet use influencing factors and helmet usage in general. The aim of this study was to examine the mediating role of traffic law enforcement and road safety education on the relationship between helmet usage influencing factors and motorcycle helmet usage. A total of 358 respondents from a university community that uses a motorcycle on daily bases to and from the community and for other important trip purposes completed a self-reported questionnaire in the Upper West Region of Ghana where motorcycles are predominantly used as a transportation mode. To test for the various hypotheses of this study, we developed a hypothesized single multiple mediated structural equation model and several sub-mediated models using AMOS 26.0. The results showed that the perceived safety of the helmet, weather conditions, and convenience of helmet use have positive significant impacts on helmet use. The study also found a full mediation role of the combined effect of traffic law enforcement and road safety education on the relationship of helmet use influencing factors investigated and helmet use. The study concludes that new traffic law enforcement and road safety education strategies need to be adopted to help improve upon the low prevalence of helmet use within the study area.